CYP11A1 silencing suppresses HMGCR expression via cholesterol accumulation and sensitizes CRPC cell line DU-145 to atorvastatin - Jiro Tashiro; Akihiro Sugiura; Tomoko Warita; Nanami Irie; Danang Dwi Cahyadi; Takuro Ishikawa; Katsuhiko Warita (Elsevier, 2023)
Statins, which are cholesterol synthesis inhibitors, are well-known therapeutics for dyslipidemia; however, some studies have anticipated their use as anticancer agents. However, epithelial cancer cells show strong resistance to statins through an increased expression of HMG-CoA reductase (HMGCR), an inhibitory target of statins. Castration-resistant prostate cancer (CRPC) cells synthesize androgens from cholesterol on their own. We performed suppression of CYP11A1, a rate-limiting enzyme in androgen synthesis from cholesterol, using siRNA or inhibitors, to examine the effect of steroidogenesis inhibition on statin sensitivity in CRPC cells. Here, we suggested that CYP11A1 silencing sensitized the statin-resistant CRPC cell line DU-145 to atorvastatin via HMGCR downregulation by an increase in intracellular free cholesterol. We further demonstrated that CYP11A1 silencing induced epithelial-mesenchymal transition, which converted DU-145 cells into a statin-sensitive phenotype. This suggests that concomitant use of CYP11A1 inhibitors could be an effective approach for overcoming statin resistance in CRPC. Moreover, we showed that ketoconazole, a CYP11A1 inhibitor, sensitized DU-145 cells to atorvastatin, although not all the molecular events observed in CYP11A1 silencing were reproducible. Although further studies are necessary to clarify the detailed mechanisms, ketoconazole may be effective as a concomitant drug that potentiates the anticancer effect of atorvastatin.